Expression and Significances of Contactin-1 in Human Gastric Cancer - Ji-Wei Yu; Sheng-Hua Wu; Rui-qi Lu; Ju-gang Wu; Xiao-Chun Ni; Gou-cai Zhou; Hai-guang Jiang; Lin-Hai Zheng; Xiao-Qiang Li; Guang-Ye Du; Bo-Jian Jiang (Gastroenterology Research and Practice)
Background. This study aimed at determining the relationship between vascular endothelial growth factor-C (VEGF-C), vascular endothelial growth factor receptor-3 (VEGFR-3), and contactin-1 (CNTN-1) expression in gastric cancer (GC). Methods. The expression level of CNTN-1 mRNA and CNTN-1 protein of 33 cases was determined using RT-PCR and Western Blot. And 105 cases were immunohistochemically examined for VEGF-C, VEGFR-3, and CNTN-1 expressions. Assessment of lymphatic vessel density (LVD) was also performed by D2-40 immunostaining. Then we analyzed the relationships between VEGF-C, VEGFR-3, and CNTN-1, as well as their correlations with clinicopathologic features, LVD, and survival time. Results. The positivity rate of VEGF-C, VEGFR-3, and CNTN-1 in primary tumor was 56.19%, 64.76%, and 58.09%. The expression of CNTN-1 significantly correlated with VEGF-C (P<0.001) and VEGFR-3 (P<0.001). All of them were closely related to TNM stage, lymphatic invasion, and lymph node involvement (P<0.05). LVD was significantly correlated with VEGF-C (P=0.001), VEGFR-3 (P=0.011), and CNTN-1 expression (P<0.001). VEGF-C, VEGFR-3, and CNTN-1 expression significantly associated with poorer prognosis (P<0.001, P=0.034, P=0.012, resp.). Conclusion. CNTN-1 associated with VEGF-C and VEGFR-3 expression in GC. All of them correlated with lymphatic metastasis, which might play an important role in the lymphatic invasion via lymphangiogenesis pathway in GC.